A Sustainable Extractive Industry Requires Educated Responsible Geoscientists - Mike Katz (Earth Science, Systems and Society)
Most geoscience undergraduate courses are technical with little regard to social responsibility and sustainable development implications. Workshop outcomes have suggested that the introduction of this content into their studies is necessary so that they can apply their technical knowledge in a responsible way. In regard to the extractive industry where most geoscientists in resource rich countries are employed, the industry’s record of social and environmental impact with non–sustainable outcomes, particularly in developing countries are evident. Important extractive industry issues such as sustainable development, corporate social responsibility, social license to operate and free, prior and informed consent for Indigenous People have attracted great attention and scrutiny in the development of industry and government policy and rightful concerns from all stakeholders. There are very few examples of these responsibility and sustainability subjects being introduced in undergraduate geoscience education except in some environmental courses in universities in North America, Europe and Australia/New Zealand, but not so well established in developing countries where there is a greater need for this content.